Observation of anomalous admixture of superconducting and magnetic fractions in BaFe2−xCoxAs2 single crystals. (22nd June 2016) - Bag, Biplab; Vinod, K; Bharathi, A; Banerjee, S S
Abstract: Increasing doping concentration ( x ) in pnictide superconductors leads to a loss of long range magnetic order and the emergence of superconductivity. In these doped compounds the role of magnetic fluctuations and their effect on superconductivity is not well understood. Below T c, in optimally doped BaFe2 −x Co x As2 single crystals at low applied magnetic fields ( H ), we observe a coexistence of regions with both positive and negative (diamagnetic) magnetization response. With increasing H the positive magnetization response weakens and the diamagnetic signal associated with superconductivity enhances. Above T c, resistivity and magnetization measurements in the normal state of the material reveals the presence of a weak diamagnetic response admixed with the magnetic response of a magnetized state. Magneto-optical imaging studies in the optimally doped sample shows a spatially inhomogeneous local magnetic response in the normal state with local regions having diamagnetic like response existing alongside magnetized regions with short range magnetic order. Above T c, the estimated volume fraction with diamagnetic fluctuations is found to be maximum in the optimally doped sample. We present a doping dependent H – T diagram identifying different fluctuation regimes. We propose our results suggest the admixture of magnetic and superconducting fractions in BaFe2 −x Co x As2 and a close correlation between them.